2017
DOI: 10.1186/s12995-017-0180-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary injury associated with spray of a water-based nano-sized waterproofing product: a case study

Abstract: BackgroundIn most reported cases of lung trauma with water proofing products, volatile organic compounds (VOC) have a prominent role. Here we report on a case involving ten workers exposed to a sprayed product containing nanoparticles in a water solution with only a few percent VOC.Case presentationTen workers suffered from respiratory symptoms following spray impregnation of hardwood furniture using a waterproofing product that contained positively charged fluorinated acrylate copolymer solid cores with a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
7
0
3
Order By: Relevance
“…For impregnation products, there are products that have a large market share and thus have frequent use, but only occasionally cause decreased lung function, or where many people are exposed and only a few develop symptoms ( Scheepers et al, 2017 , Cormican and Rees, 2006 ). The explanation for this could have to do with dosimetry, i.e.…”
Section: Biological Applicability Domain Of Aop 302mentioning
confidence: 99%
See 1 more Smart Citation
“…For impregnation products, there are products that have a large market share and thus have frequent use, but only occasionally cause decreased lung function, or where many people are exposed and only a few develop symptoms ( Scheepers et al, 2017 , Cormican and Rees, 2006 ). The explanation for this could have to do with dosimetry, i.e.…”
Section: Biological Applicability Domain Of Aop 302mentioning
confidence: 99%
“…Respiratory symptoms following exposure to airborne substances (chemicals or particles) are reported regularly. In private homes, impregnation products are among the most commonly reported triggers of such symptoms ( Lazor-Blanchet et al, 2004 , Vernez et al, 2006 , Khalid et al, 2009 , Scheepers et al, 2017 , Tashiro et al, 1998 , Duch et al, 2014 , Laliberté et al, 1995 , Burkhart et al, 1996 , Malik and Chappell, 2003 ). In occupational settings, respiratory clinical signs of toxicity have been observed after workers’ exposure to cleaning products ( Clausen et al, 2020 , Medina-Ramon et al, 2006 , Vizcaya et al, 2015 ) and pesticides ( Slavica et al, 2018 ), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to polyacrylate nanoparticles was found associated with pleural effusion, pulmonary fibrosis, and granuloma among seven female workers working in a print plant 155 . Another study showed severe chemical pneumonitis with extensive bilateral ground-glass opacities in a worker exposed to nanosized positively charged fluorinated acrylate during spray painting wooden furnitures 156 . In a cross-sectional study on 28 workers of a Chinese manufacturing industry, Li and colleagues (2018) 157 reported a significant reduction in lung function of the workers as a result of long-term exposure to nanosized calcium carbonate.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…W badaniach laboratoryjnych u części pacjentów wykazano leukocytozę [68]. W wykonanych badaniach w zależności od stanu klinicznego obserwowano hipoksję [68], zaburzenia restrykcyjne w badaniu spirometrycznym oraz obniżenie zdolności dyfuzyjnej [69].…”
Section: Ostre Uszkodzenie Płuc Po Użyciu Impregnatów (Water-repellenunclassified